Poetic imagination in Proverbs: Variant repetitions and the nature of poetry - Heim, Knut Martin (U.S.A, 2013)
No fewer than 223 verses in Proverbs appear two times (79 sets), three times (15 sets), or even four times (5 sets) in identical or slightly altered form--more than 24% of the book. Heim analyzes all these, presenting them in delineated Hebrew lines and English translations. Where appropriate, the translations are followed by textual notes that discuss uncertainties regarding the textual witnesses (textual criticism) and explore lexical, grammatical, and syntactical problems. Heim also analyzes the way the parallelism in each verse of a variant set has been constructed, presenting diagrams and tables with columns that highlight the corresponding similarities and differences among repeated verses. Key to this investigation is the search for links between the variants and their surrounding verses, such as repetitions of sound and sense. Heim shows that most variant repetitions result from skillful poetic creativity. Reconstruction of the editorial and creative poetic process highlights what poets did, how they did it, and why they did it. He develops criteria for determining the direction of borrowing between the verses and demonstrates that the phenomenon of variant repetition is an editorial concern that operates on the level of the book as a whole. He develops and refines a range of interpretive techniques and skills, arrives at fresh interpretations, and shows that ancient proverbial wisdom is relevant to modern societies. This study sheds new light on the nature of biblical poetry and the methods and virtues best suited for its study. While specific to the book of Proverbs in the first instance, the findings in this study apply to poetry elsewhere. Three fundamental insights should inform future work on poetry: the creative combination of repetition with variation is the very essence of poetry
Keywords: Religion -- Biblical Studies -- Old Testament